Analisa Etika Bisnis Islam Terhadap Praktek Sewa Menyewa Kamar Kost : Studi Kasus Kelurahan Mekar Baru Kecamatan Kota Kisaran Barat - Nurwandri, Andri; Sari, Ika Permata (Pusdikra Publishing, 2024)
In general, renting out boarding rooms is a component of the corporate world, which is expanding significantly across all industries. The purpose of this study is to ascertain the regularity of boarding room rentals. Find out how muamalah fiqh analysis relates to the practice of renting daily boarding rooms in Mekar Baru Village, Kota Kisaran Barat District, Asahan Regency is the formulation used in this research. In addition, a review of muamalah fiqh regarding the practice of renting boarding rooms that are still in the first party tenancy period in Mekar Baru Village, Kisaran City District, and a problem formulation regarding the status of boarding room utilization factors during the rental period in Kota Kisaran Barat District, Asahan Regency are addressed in this research Asahan Regency, West.All data or references that have been collected are analyzed and rearranged, and in this case, rental practice uses a descriptive analytical approach. The study's findings suggest that it is against Islamic law and the terms of the ijarah contract for certain locations in Mekar Baru Village, Kota Kisaran Barat District, Asahan Regency, to rent out boarding rooms to outside parties. Practices that take place between the owner and the third-party tenant, or second tenant, do not adhere to the principles, requirements, or aspects of ijarah. Since the original renter still has the right to rent the room, the owner of the boarding room rental should pay the first tenant after being open and honest with them about any transactions they do with other parties.